The development of a performance analysis system for freestyle swimming start performances in adolescent male swimmers - Dormehl, S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
This study aimed to develop a notational analysis system to identify key performance indicators in freestyle starts using adolescent males in competition. Ultimately 19 performance indicators, split into five phases, were described and refined following discussion with expert coaches. Overall Cohen`s Kappa values for reliability were acceptable (0.66 - 0.72) according to published sport-determined thresholds, despite definition interpretation discrepancies and difficulties in observing post-event video footage, reducing intra-operator reliability in some performance indicators. Operator experience improved inter-operator reliability. Six performance indicators appeared to contribute most to faster 15 m start times, although it was also apparent that the inclusion of the underwater phase would be relevant to any future studies when providing feedback to coaches.